Sino-US TV program for children. - Zhang Lei (Beijing Review, 1998)
I Love Science, broadcast on China Education TV, is a series of 200 episodes produced for children of 8 to 12 years old that presents science in an entertaining way. Hosted by three Chinese children, the program examines areas such as plants, animals, human society, energy, climate, the earth, and the universe.